ATG4B Inhibitor UAMC-2526 Potentiates the Chemotherapeutic Effect of Gemcitabine in a Panc02 Mouse Model of Pancreatic Ductal Adenocarcinoma - Takhsha, Farnaz Sedigheh; Vangestel, Christel; Tanc, Muhammet; De Bruycker, Sven; Berg, Maya; Pintelon, Isabel; Stroobants, Sigrid; De Meyer, Guido R. Y.; Van Der Veken, Pieter; Martinet, Wim (Frontiers in Oncology, 2021)
Resistance against anti-cancer therapy is one of the major challenges during treatment of multiple cancers. Gemcitabine is a standard first-line chemotherapeutic drug, yet autophagy is highly activated in the hypoxic microenvironment of solid tumors and enhances the survival of tumor cells against gemcitabine chemotherapy. Recently, we showed the add-on effect of autophagy inhibitor UAMC-2526 to prevent HT-29 colorectal tumor growth in CD1-/- Foxn1nu mice treated with oxaliplatin. In this study, we aimed to investigate the potential beneficial effects of UAMC-2526 in a syngeneic Panc02 mouse model of pancreatic ductal adenocarcinoma (PDAC). Our data showed that UAMC-2526 combined with gemcitabine significantly reduced tumor growth as compared to the individual treatments. However, in contrast to in vitro experiments with Panc02 cells in culture, we were unable to detect autophagy inhibition by UAMC-2526 in Panc02 tumor tissue, neither via western blot analysis of autophagy markers LC3 and p62, nor by transmission electron microscopy. In vitro experiments revealed that UAMC-2526 enhances the potential of gemcitabine to inhibit Panc02 cell proliferation without obvious induction of cell death. Altogether, we conclude that although the combination treatment of UAMC-2526 with gemcitabine did not inhibit autophagy in the Panc02 mouse model, it has a beneficial effect on tumor growth inhibition.